Philosophy and science fiction - French, Peter A.; Wettstein, Howard K. (Malden, MA Wiley Periodicals, Inc., 2015)
"Science Fiction and Philosophy deals with science-fictional thought experiments and their long history in philosophy, with roots back to the mythological inventions of ancient philosophers such as Plato and Zhuangzi. These thought experiments play a prominent role especially in current metaphysical theorizing about personal identity, artificial minds, and the nature of time. This issue includes reflections on the nature of science fiction, on the epistemology of science fictional thought experiments, on our possible moral and social relationships with future intelligent beings, on the prospects of human or post-human self-transformation, and on time travel. While most of the contributions are expository essays written in the typical style of journal articles, two of the contributions are original short stories written by prominent SF writers whose writing is informed by the advanced graduate work they have done in philosophy" -- Provided by publisher.
"But is it science fiction?": science fiction and a theory of genre / Simon J. Evnine -- Improve your thought experiments overnight with speculative fiction! / Ross P. Cameron -- Fact, fiction, and fantasy / Ben Blumson -- The epistemic value of speculative fiction / Johan De Smedt, Helen De Cruz -- The alienation of humans and animals in uplift fiction / Ina Roy-Faderman -- A defense of the rights of artificial intelligences / Eric Schwitzgebel, Mara Garza -- "This endless space between the words": The limits of love in Spike Jonze's her / Troy Jollimore -- Metaphysical daring as a posthuman survival strategy / Pete Mandik -- Nowhere man: time travel and spatial location / Sara Bernstein -- Speculative fiction and the philosophy of perception / Brian L. Keeley -- Philosophical science fiction: intelligent gorilla comes to Shabbos dinner / Eric Linus Kaplan -- Crash space / R. Scott Bakker.
Includes bibliographical references.
Keywords: Science fiction -- History and criticism; Science fiction -- Philosophy; Philosophy in literature